Evolution and structural transition of quasicrystalline phases in Al-Fe-Cu-Cr and Al-Fe-Cu-Mn alloys during high energy ball milling - Yadav, T.P.; Mukhopadhyay, N.K.; Tiwari, R.S.; Srivastava, O.N. (Institute of Physics Publishing, 2010)
The main objective of the current work was to investigate the transformation mechanism in quasicrystals during mechanical alloying/milling. The quasicrystalline phases have been synthesized by melting the individual elements as well as by mechanical alloying of the concerned elements using high energy ball milling. The transformation of icosahedral and decagonal quasicrystalline phases to various disordered states in Al-Fe-Cu-Cr and Al-Fe-Cu-Mn alloys during milling of the pre-alloyed material. The milling of a quasicrystalline alloy was carried out using a high energy ball mill by varying milling times up to 40h under liquid hexane medium and at various milling intensity. X-ray diffraction was carried out for evaluating the lattice strain, lattice parameters and crystallite sizes of the mechanically milled samples. The evolution of nano icosahedral and nano decagonal phases as well as crystalline phases was found to occur. The subsequent thermal treatment led to the structural ordering in the concerned phases. The implication of the evolution of various phases, their structural correlations and their relative stability will be discussed.
Keywords: Alloying elements; Quasicrystalline alloys; Quasicrystalline phasis; Structural transitions